In situ Polymerization of Polyamide 6/Boron Nitride Composites to Enhance Thermal Conductivity and Mechanical Properties via Boron Nitride Covalently Grafted Polyamide 6. Issue 4 (8th January 2020) - Fang, Hui; Li, Denghui; Wu, Fangjuan; Peng, Xiangfang; Chen, Anlin; Zhang, Lingjie; Chen, Sheng
Abstract : Polyamide 6/boron nitride (PA6/BN) composites were synthesized via anionic ring‐opening polymerization using ε‐caprolactam as the monomer and functional boron nitride (f‐BN) as the thermal conductive filler. Besides the homopolymerized PA6, some PA6 molecule chains would grow from the f‐BN sheets through the "grafting from" strategy. Compared with unfunctional hexagonal BN (h‐BN), the introduction of f‐BN not only improved the dispersion of f‐BN in the matrix but also enhanced the interface bonding between f‐BN and PA6. The homogeneous dispersion of f‐BN in the PA6/f‐BN composite favored the formation of the continuous thermal conductive paths or network at a low f‐BN loading, and the good interface bonding reduced the phonon scattering in the interface, which improved the thermal conductivity (TC) of the PA6/f‐BN composite by 66.0% compared with that of the pure PA6, when only 5 wt% f‐BN was added. In contrast, with the same content of unfunctional h‐BN loading, the TC of the corresponding composite merely improved by 29.7%. Moreover, Young's modulus and yield strength of PA6/f‐BN composites had increased obviously with the introduction of f‐BN, whereas those of PA6/h‐BN composites showed small fluctuation with the same contents of BN. POLYM. ENG. SCI., 60:710–716, 2020. © 2020 Society of Plastics Engineers